Bystander Reporting on a College Campus: Moral Intuitions as a Precursor to Informal Social Control. Issue 3 (4th March 2023) - Silver, Eric
ABSTRACT: Research in criminology finds that moral intuitions influence both offending and punitive reactions to offending. However, no prior studies have examined the influence of moral intuitions on bystander reporting. To fill this gap, I examine the influence of moral intuitions on bystanders' likelihood of engaging in indirect informal social control by reporting a range of deviant behaviors to campus authorities. Deviant behaviors include common deviance (cheating on college work), uncommon deviance (theft and property damage), and dangerous deviance (alcohol induced unconsciousness and attempted rape). Using a large sample of college students (N = 1, 593), I find that respondents with strong individualizing moral intuitions that emphasize care for the vulnerable, are more likely to report dangerous deviance while respondents with strong binding moral intuitions that emphasize social order and cohesion, are more likely to report both dangerous deviance and uncommon deviance. I also find that respondents' moral intuitions have no bearing on their likelihood of reporting common deviance. Finally, I find that for dangerous deviance, moral intuitions and gender interact in unexpected ways. This study provides compelling evidence that a moral intuitionist approach is useful for studying bystander reporting as a form of informal social control and suggests new directions for theoretical advancement.